Hubungan Tingkat Pengetahuan K3 Dengan Sikap Terhadap Pemakaian APD Pada Pekerja Di Sentra Industri Pande Besi Desa Padas Kecamatan Karanganom Kabupaten Klaten - Prasetyo, Ardiansah Eko; , Tarwaka, PGDip.Sc.,M.Erg; , Kusuma Estu W .S.KM, M.Kes (2016)
Personal protective equipment (PPE) is a set of safety equipment used by workers to protect all or part of his body from possible exposure to the potential hazards of the work environment against accidents and occupational diseases. Knowledge is one of the factors that affect workers in the use of PPE. If the workers have good knowledge, then the worker will use apd well too. The purpose of this study to determine the relationship K3 knowledge level attitudes toward the use of Personal Protective Equipment (PPE) for workers at Sentra Industry Pande Besi village Padas Karanganom Klaten district. The results of statistical tests that are known to determine the relationship of the level of K3 knowledge with attitudes towards the use of PPE obtained using Chi Square test p-value = 0.012 (p-value <0.050). It can be explained that the knowledge K3 has a relationship attitudes towards the use of PPE.